Progress in cryptology -- AFRICACRYPT 2018 : 10th International Conference on Cryptology in Africa, Marrakesh, Morocco, May 7-9, 2018, Proceedings /: 10th International Conference on Cryptology in Africa, Marrakesh, Morocco, May 7-9, 2018, Proceedings. (2018) - Unknown
No abstract available